Analisis Pelaksanaan Manajemen Pelayanan Kesehatan Peduli Remaja - Novi Yanti (STIKes Hang Tuah Pekanbaru, 2014)
Teens encounter natural changes which often cause unexpected serious impacts, such as the increasing rate of abortion cases, unwanted pregnancies, and sexually transmitted diseases. Cited from WHO, developed countries are more likely to have the highest rate of teen’s sexuality. Pekanbaru is a city with the highest rate of teen’s sexuality in Riau. In the context of overcoming the problems on teenagers and eliminating HIV/AIDS cases as the focus of MDG’s 2015, the Health Department is in charge of implementing Health Service on Teens Care (abbreviated in Indonesian, PKPR). This is a qualitative research conducted from June 29 to July 17, 2012. In-depth Interview on eight persons was conducted, and ten teens suspected in teen’s sexuality participated in Focus Group Discussion (FGD). Based on the input component result, there is no particular government regulation on teen’s problems. There are already responsible persons for the health workers and for each activity, and the guidebook from the Ministry of Health of Indonesia. On the other hand, particularly allocated budget for PKPR is not yet specified. Since it is still merged with the one allocated for other programs, there are limited activities are possibly conducted, and limited counseling patterns. Then, the process component result shows that advocacy is already performed. There are socialization, training, and counseling for teenagers, and also screening program for school students. Monitoring and evaluation format are arranged even though the data entry process is not in line with the specified format. Based on output component result, the implementation of PKPR accomplished only 0.32% from 80% targeted. In accordance with this research, Pekanbaru Health Department is considered requiring special division on teens care in order to design implementation SOPs based on the existing problems at Health Centers